Unravelling the widening of the earliest Andean northern orogen: Maastrichtian to early Eocene intra‐basinal deformation in the northern Eastern Cordillera of Colombia. (9th August 2020) - Bayona, Germán; Baquero, Mauricio; Ramírez, Catalina; Tabares, Manuela; Salazar, Ana M.; Nova, Giovanny; Duarte, Edward; Pardo, Andrés; Plata, Angelo; Jaramillo, Carlos; Rodríguez, Guillermo; Caballero, Victor; et al.
Abstract: The onset of deformation in the northern Andes is overprinted by subsequent stages of basin deformation, complicating the examination of competing models illustrating potential location of earliest synorogenic basins and uplifts. To establish the width of the earliest northern Andean orogen, we carried out field mapping, palynological dating, sedimentary, stratigraphic and provenance analyses in Campanian to lower Eocene units exposed in the northern Eastern Cordillera of Colombia (Cocuy region) and compare the results with coeval succession in adjacent basins. The onset of deformation is recorded in earliest Maastrichtian time, as terrigenous detritus arrived into the basin marking the end of chemical precipitation and the onset of clastic deposition produced by the uplift of a western source area dominated by shaly Cretaceous rocks. Disconformable contacts within the upper Maastrichtian to middle Palaeocene succession document increasing supply of quartzose sandy detritus from Cretaceous quartzose rocks exposed in eastern source areas. The continued unroofing of both source areas produced a rapid shift in depositional environments from shallow marine in Maastrichtian to fluvial‐lacustrine systems during the Palaeocene‐early Eocene. Supply of immature Jurassic sandstones from nearby western uplifts, together with localized plutonic and volcanic Cretaceous rocks, caused a shift in Palaeocene sandstones composition from quartzarenites to litharenites. Supply of detrital sandy fragments, unstable heavy minerals and Cretaceous to Ordovician detrital zircons, were derived from nearby uplifted blocks and from SW fluvial systems within the synorogenic basin, instead of distal basement rocks. The presence of volcanic rock fragments and 51–59 Ma volcanic zircons constrain magmatism within the basin. The Maastrichtian–Palaeocene sequence studied here documents crustal deformation that correlates with coeval deformation farther south in Ecuador and Peru. Slab flattening of the subducting Caribbean plate produced a wider orogen (>400 km) with a continental magmatic arc and intra‐basinal deformation and magmatism. Abstract : The Maastrichtian ‐ Paleocene sequence studied in the Cocuy area and adjacent basins documents crustal intra‐basinal deformation since Maastrichtian. Slab flattening of the subducting Caribbean plate produced a wider orogen (>400 km) with a continental magmatic arc and intra‐basinal deformation and magmatism.